Atypical diabetes arising from SHORT syndrome: a case report - Wang, Aili; Xu, Miao; Li, Li; Li, Jialin (Frontiers in Endocrinology, 2024)
Short stature, joint hyperextension, ocular hypotension, Rieger abnormalities, and delayed tooth eruption (SHORT) syndrom is a rare primary autosomal dominant genetic disorder mainly caused by pathogenic loss-of-function variants in the phosphoinositide-3-kinase regulatory subunit 1 (PIK3R1) gene. We report the case of a Chinese adult female patient with SHORT syndrome, carrying a PIK3R1 gene variant (c.1945C > T), who developed abnormal glucose metabolism and severe postprandial insulin resistance over 9 years. Although there are currently no established treatment guidelines for insulin resistance in patients with SHORT syndrome, we implemented a comprehensive treatment plan, including lifestyle interventions, metformin, and voglibose for glucose control. After 6 months of continuous observation, the patient's blood glucose levels and insulin resistance improved significantly. This case study provides useful insights for future treatment strategies.